Exploration for Triatoma virus (TrV) infection in laboratory-reared triatomines of Latin America: a collaborative study - Marti, Gerardo Anibal (2013)
Triatoma virus (TrV) is a small, non-enveloped virus that has a +ssRNA genome and is currently classified under the Cripavirus genus of the Dicistroviridae family. TrV infects haematophagous triatomine insects (Hemiptera: Reduviidae), which are vectors of American Trypanosomiasis (Chagas disease). TrV can be transmitted through the horizontal fecal-oral route, and its infection causes either deleterious sublethal effects or even death of laboratory insect colonies. Various species of triatomines from different regions of Latin America are currently being reared in research laboratories, with little or no awareness of the presence of TrV; therefore, any biological conclusion drawn from experiments on insects infected with this virus is inherently affected by the side effects of its infection. In this study, we developed a mathematical model to estimate the sample size required for detecting a TrV infection. We applied this model to screen the infection in feces of triatomines belonging to insectaries from 13 Latin American countries, carrying out the identification of TrV by using reverse transcriptase PCR. TrV was detected in samples coming from Argentina, which is the country where several years ago the virus was first isolated from Triatoma infestans (Hemiptera: Reduviidae). Interestingly, several colonies from Brazil were also found infected with the virus. This positive result widens the TrV?s host range to a total of 14 triatomine species. Our findings suggest that many triatomine species distributed over a large region of South America may be naturally infected with TrV.